PENGARUH PEMBERIAN PERMEN KARET TERHADAP LAMA WAKTU MENAHAN RASA HAUS PASIEN YANG MENJALANI HEMODIALISIS DI RSUD Dr. M. HAULUSSY AMBON - Fajar Sodik; abdul Thalib (Pasapua Health Journal, 2019)
Introduction: Patients with chronic kidney failure who are undergoing hemodialysis experience complaints of thirst and dry mouth. Management of thirst that can be done in patients with chronic kidney failure include chewing gum. The purpose of this study was to determine the effect of gum administration on the length of time holding back the thirst of patients with chronic renal failure who underwent hemodialysis in the RSUD Dr. M. Haulussy Ambon. Method: The research design used was quasi-experimental with a pre-test design and post-test design. The research design used the test before and after treatment on the respondents. The population were all patients with chronic renal failure who underwent hemodialysis at the RSUD Dr. M. Haulussy Ambon which amounted to 42 with a total sampling technique. Results: 42 respondents, the length of time to hold thirst for respondents without chewing gum during the pre-test with an average of 59.69 minutes and for the respondents by chewing gum during the post-test test with an average of 105.17 minutes . From the results of data analysis with statistical tests paired sample t-test obtained significant results with a p value of 0,000. Conclusion: That there is an effect of giving chewing gum to the taste response must be patients with chronic